Manajemen Strategi Pemasaran Pendidikan Dalam Meningkatkan Minat Masyarakat Di Sekolah Menengah Atas Negeri 4 Tanjung Jabung Timur - farida farida; Darma Putra; Try Susantiq (Fakultas Keguruan dan Ilmu Pendidikan - Universitas Gresik, 2022)
Marketing Strategy in an educational institution is a renewal step that must be done when there are tight rivals in getting customers. Educational marketing can be done to provide information to the public about school products, increase public interest and interest in school products and distinguish school products from other school products. The purpose of this study is to find out the marketing strategy carried out at SMAN 4 Tanjung Jabung Timur, want to implement the marketing strategy at SMAN 4 Tanjung Jabung Timur and want to know the inhibiting factors. Based on this research, this study aims to find out educational Marketing Strategy in an educational institution is a renewal step that must be done when there are tight rivals in getting customers. Educational marketing can be done to provide information to the public about school products, increase public interest and interest in school products and distinguish school products from other school products. The purpose of this study is to find out the marketing strategy carried out at SMAN 4 Tanjung Jabung Timur, want to implement the marketing strategy at SMAN 4 Tanjung Jabung Timur and want to know the inhibiting factors. Based on this research, this study aims to find out educational services is carried out in two ways, namely directly and directly, while the educational marketing strategy at SMAN 4 Tanjung Jabung Timur which is carried out is characterized by the presence of products, prices, locations, HR, services and processes. So that these components are easily recognized by the public as users of educational services.